2023
DOI: 10.3389/fnut.2022.1073782
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nutritional assessment tools in the critically ill patient: A systematic review

Abstract: BackgroundAmong the risks of the critically ill patient, one of the aspects to be taken into account is the high probability of occurrence of malnutrition risk (40–50%). This process leads to increased morbimortality and worsening. The use of assessment tools allows the individualization of care.ObjectiveTo analyze the different nutritional assessment tools used during the admission of critically ill patients.MethodsSystematic review of the scientific literature related to the nutritional assessment of critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The results of our study indicate that the nurses’ functions were more related to the onset of EN, its management and defense (such as early onset) [ 46 , 46 , 48 , 49 , 51 , 52 , 56 , 61 ], not showing an assessment at the admission of the nutritional status of the patients or using the tools proposed by ASPEN, ESPEN or scientific evidence [ 16 , 18 , 22 , 25 , 68 ]. These findings coincide with the scientific literature [ 19 , 63 , 65 , 68 ], where it is shown that nurses consider nutritional care less important and do not take into account the application of scales or instruments to assess whether or not patients are at risk of malnutrition. In addition, the highest knowledge scores were associated with the items on the implementation of interventions (initiation of EN, management of EN), followed by the prevention of complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that the nurses’ functions were more related to the onset of EN, its management and defense (such as early onset) [ 46 , 46 , 48 , 49 , 51 , 52 , 56 , 61 ], not showing an assessment at the admission of the nutritional status of the patients or using the tools proposed by ASPEN, ESPEN or scientific evidence [ 16 , 18 , 22 , 25 , 68 ]. These findings coincide with the scientific literature [ 19 , 63 , 65 , 68 ], where it is shown that nurses consider nutritional care less important and do not take into account the application of scales or instruments to assess whether or not patients are at risk of malnutrition. In addition, the highest knowledge scores were associated with the items on the implementation of interventions (initiation of EN, management of EN), followed by the prevention of complications.…”
Section: Discussionmentioning
confidence: 99%
“…This https://jicem.journals.ekb.eg/ was in agreement with Ferrie, et al [14] who reported that there was a significant relation between SGA and the need to MV with a higher SGA score was significantly associated with more days of MV. Also, Domenech-Briz V, et al [13] reported that, SGA-C, decreased TSF and MAC were significantly associated with additional days of MV.…”
Section: Aki: Acute Kidney Injurymentioning
confidence: 95%
“…There was a significant association between the advanced grade of SGA (grade C) and the need to MV (p-value 0.001). (Table 4) Individuals may also observe a decrease in body weight, up to 10 kg, based on the LOS [13] .…”
Section: Aki: Acute Kidney Injurymentioning
confidence: 99%
“…The recent guidelines from the American Society for Parenteral and Enteral Nutrition (ASPEN) recommend classifying nutritional risk using assessment tools such as Nutrition Risk Screening 2002 (NRS 2002), the Malnutrition Universal Screening Tool (MUST), the Nutrition Risk in the Critically Ill score (NUTRIC), or its modified version (mNUTRIC), to ascertain baseline nutritional status and to inform individualized nutritional management 4 . The mNUTRIC, widely used and validated across numerous clinical studies, correlates with clinical outcomes including mortality and adverse events in the intensive care unit 16 18 . In critically ill patients with an mNUTRIC score of ≥ 5, early caloric supplementation has been linked to reduced mortality and morbidity by providing higher energy and protein, and by facilitating the rapid achievement of caloric goals 19 22 .…”
Section: Introductionmentioning
confidence: 99%